UNVEILING THE SILENT STRUGGLE: DOMESTIC VIOLENCE AMONG MARRIED KOM WOMEN, MANIPUR - Marem, Reineichim; Oinam, Subhaarati; Singh, S. Dharmen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
his study examines the prevalence and nature of domestic violence among married Kom women in Manipur, India. Using a mixed-methods approach, the research combines quantitative survey data from 100 women with qualitative interviews from 20 participants. The findings reveal a high prevalence of psychological and economic violence, with approximately 75% of respondents reporting these forms of abuse. Physical violence was reported by 35% of participants. The study identifies several key factors contributing to domestic violence, including alcohol abuse, economic dependency, and deeply ingrained cultural expectations that pressure women to endure abuse for the sake of family cohesion. The research highlights the complex interplay between psychological, economic, and physical abuse, exacerbated by substance abuse and financial control within households. The study also explores coping strategies employed by women and the challenges they face in seeking help due to social stigma and lack of support systems. The findings emphasize the need for a multi-dimensional approach to intervention, including economic empowerment programs, addiction support, community-based initiatives, and efforts to challenge patriarchal norms. This research contributes to the understanding of domestic violence in rural and tribal contexts, providing insights for policy development and targeted interventions.